Selective copper(II) removal using molecularly imprinted alginate-metformin hydrogel beads: Mechanistic insights from isotherms, DFT and molecular docking - Fallah, Amirhossein; Oladipo, Akeem Adeyemi; Khosravi, Foroogh; Pirgalioglu, Saltuk (Elsevier, 2025)
A copper(II)-imprinted hydrogel (Cu-Imp) was developed using sodium alginate and metformin hydrochloride to fabricate structurally selective polymeric beads for efficient Cu(II) removal from aqueous solutions. The imprinting strategy leveraged the coordination chemistry of Cu(II) with nitrogen donors from metformin and carboxylate groups from alginate to construct high-fidelity recognition sites. Experimental characterization confirmed morphological refinement (SEM), selective Cu uptake (EDX), and functional group interaction (FTIR). The Cu-Imp beads achieved a maximum adsorption capacity of 50.21 mg/g and a Cu(II) removal efficiency of 96.3 % at an initial concentration of 10 mg/L. Isotherm modeling indicated strong agreement with the Redlich-Peterson (R-2 = 0.948) and Koble-Corrigan (R-2 = 0.947) models, suggesting heterogeneous monolayer-multilayer adsorption. Kinetic analysis revealed pseudo-second-order and Elovich models as the best fit (R-2 = 0.986-0.997), confirming chemisorption with a rate-limiting electron-sharing mechanism. Molecular docking revealed favorable Cu-OH binding orientations, while DFT calculations validated strong Cu-O/N coordination at pH 5.4, with an adsorption energy of -60.34 kcal/mol and a HOMO-LUMO gap of 0.087 eV, indicating high electronic reactivity. The material demonstrated excellent regeneration capacity, maintaining similar to 26.8 mg/g performance over five cycles. Together, these findings confirm the success of the molecular imprinting strategy and its potential for designing next-generation, reusable, and ion-selective adsorbents for water purification applications.
Keywords: Molecular imprinting; Alginate beads; Metformin; Copper(II) removal; Docking; Quantum-level insight; Isotherms